Mergers, acquisitions and strategic alliances: understanding the process - Gomes, Emanuel; Weber, Yaakov; Brown, Chris; Tarba, Shlomo Yedidia (Basingstoke, 2011)
"Drawing on the unique academic and practical experience of its authors, Mergers, Acquisitions & Strategic Alliances takes a detailed look at the strategic, financial and procedural aspects of planning and executing mergers, acquisitions and strategic alliances. Unlike other books in this area, it explores the similarities and differences between these three business options, outlining the various scenarios in which one strategy is preferable to the other when approaching corporate restructuring. Comprehensive international case studies are integrated throughout the text to demonstrate the real-world application of the theory presented."